Chirality induction using circularly polarized light into a branched oligofluorene derivative in the presence of an achiral aid molecule. Issue 9 (18th December 2015) - Wang, Yue; Kanibolotsky, Alexander L.; Skabara, Peter J.; Nakano, Tamaki
Abstract : Chirality induction into a uniform, star-shaped fluorene oligomer with a central truxene moiety (T3) was achieved using circularly polarized light in the presence of achiral fluorene or phenanthrene. Abstract : Chirality induction into a uniform, star-shaped fluorene oligomer with a central truxene moiety (T3) was achieved using circularly polarized light in the presence of achiral fluorene or phenanthrene. Induction into T3 alone was difficult, suggesting that close chain packing realized through interactions of T3 with small molecules plays a role in chirality induction.